Blood slaves - Redmond, Markus, 1974- (Redmond, Markus, 1974- Blood saga, 2025)
"In the Province of Carolina, 1710, freedom seems unattainable for Willie, for his beloved Gertie, and for their unborn child. They live, suffer, and toil under their brutal master, James "Big Jim" Barrow, whose grand plantation was built by the blood, sweat, and tears of the enslaved. To flee this hell on earth is be hunted and killed. Until one strange night Willie is offered a dark hope by Rafazi, an enigmatic slave with an irresistible and blood-chilling path to liberation. Hailing from the Kingdom of Ghana, Rafazi is the lone survivor of the Ramanga, an African vampire tribe rendered nearly extinct by plague. Rafazi has roamed the world for centuries with an undying desire to replenish the power that once defined his heritage. In Willie, Rafazi has found his first biddable subject to be turned and to help in a hungry revolt. And Willie desires nothing more than to free his people from malicious bondage. Whatever it takes. One by one, as an army of blood slaves thirsting for revenge is gathered, the headstrong Gertie fears that no good can come from the vampiric legacy that courses through Rafazi's veins. Willie knows that only evil can fight evil. And when the woman he loves stands between the reemergence of the Ramanga and the justified slaughter of the oppressors, Willie must make an irreversible decision. Only one thing is certain: on the Barrow plantation, and beyond, blood will spill. Part historical drama, part supernatural horror, and part alternate history, Blood Slaves is an ingenuous and defiant new creation myth of the vampire, one rooted in both justice and the sometimes-violent means necessary to achieve it"--